Perspectives of parents of adolescents with repeated non-suicidal self-injury on sharing their caretaking experiences with peers: a qualitative study - Qin, Yuan; Wu, Dongmei; Liu, Jiao; Peng, Jianyan; Li, Chunya (Frontiers in Psychiatry, 2023)
The prevalence of non-suicidal self-injury among adolescents has increased over the years. Most parents, however, are poorly informed and confused about this behavior. Sharing caretaking experiences with parents in similar situations seems to be beneficial. Nevertheless, few researchers have explored the views of parents who share their caretaking experiences with peers.Aim: This study aimed to investigate the perspectives of parents of adolescents with repeated nonsuicidal self-injury on sharing their caretaking experiences with peers as well as the motivations for and barriers to this behavior.Methods: This qualitative study adopted a purposive sampling method. Participants (16 mothers and 2 fathers) were recruited from the mental health center of a tertiary hospital in Chengdu, Sichuan, China. A total of 18 semistructured face-to-face individual interviews were conducted. All interviews were audio-recorded and analyzed thematically using NVivo 11.Results: Three themes and nine subthemes were identified: (1) sharable caretaking experiences: reflection and transformation, self-emotional management, and diversified support; (2) motivations for sharing: empathy, reciprocity, and meaning; (3) barriers to sharing: inadequate knowledge, low self-identity, and concerns for children. Parents accumulate a wealth of experience during their long-term care of adolescents with repeated non-suicidal self-injury. Although most parents are willing to share their caretaking experiences with peers, there are several barriers. Therefore, in order to increase parents' motivation to share, psychological education is necessary.